Defendant and Victim Sex, Sexism, and Decision Making in an Ambiguous Assault Case. Issue 5 (19th October 2016) - Cox, Jennifer; Kopkin, Megan R.
Abstract : The aim of the present study was to better understand how the sex of a defendant and of a victim in an ambiguous assault case impact juror verdicts and perceptions of the defendant. Juror sexist attitudes and the impact of these beliefs on decision making were also investigated. Mock jurors completed a measure of sexist attitudes and read a brief summary of an assault case in which the sexes of the defendant and victim were manipulated. Participants then rendered a verdict and provided sentencing recommendations. Mock jurors recommended the harshest sentence for the male defendant who assaulted a female victim. However, the female defendant, regardless of victim sex, was perceived as more psychopathic. Results are discussed in terms of the selective chivalry theory of sexism.